Density-dependent regulation of breeding success in the Red-crested Pochard Netta rufina. Issue 1 (2nd January 2018) - Poláková, Klára; Musil, Petr; Musilová, Zuzana; Zouhar, Jan
ABSTRACT: Capsule: Numbers of breeding Red-crested Pochard Netta rufina in the Czech Republic were positively correlated with reproductive success in the previous year, yet annual productivity, declined with increasing numbers of females at the beginning of the breeding season, suggesting local limiting factors on this population. Aims: To test the hypothesis that long-term increases in numbers of a breeding population of Red-crested Pochard Netta rufina can be explained by the productivity (numbers of ducklings fledged) in the previous year. We also test for the potential adverse effect of population size on population productivity in the current year. Methods: Data from 2004 to 2016 from South Bohemia, Czech Republic, were analysed using TRends and Indices for Monitoring Data software to investigate changes in numbers of adults, numbers of females at the start of the breeding season and number of broods produced. Results: There was a significant increase in the numbers of adults and females at the beginning of each breeding season. Numbers of adults in May positively correlated with productivity (numbers of ducklings fledged) in the previous breeding season, but relative productivity (broods per adult female) in the current year was negatively correlated with females abundance at the beginning of the breeding season. Conclusions: The study identifies density-dependent regulation as a factor in the population productivity of Red-crested Pochards using intensively managed fishponds as a breeding ground.